Dermatoscopic fi ndings as a complementary tool in the differential diagnosis of the etiological agent of tinea capitis - Regina Casz Schechtman; Nanashara Diane Valgas Silva; Maria Victória Quaresma; Fred Bernardes Filho; Alice Mota Buçard; Celso Tavares Sodré (Sociedade Brasileira de Dermatologia, 2015)
AbstractTinea capitis is a scalp infection caused by fungi. In Brazil, the main causative agents are Microsporum canis and the Trichophyton tonsurans. Etiological diagnosis is based on suggestive clinical findings and confirmation depends on the fungus growth in culture. However, it is not always possible to perform this test due to lack of availability. We reveal the dermoscopic findings that enable distinction between the main causative agents of Tinea capitis, M. canis and T. tonsurans. The association of clinical and dermatoscopic findings in suspected Tinea capitis cases may help with the differential diagnosis of the etiological agent, making feasible the precocious, specific treatment.